PERAN UNIT TURJAWALI SATUAN SAMAPTA POLRES SORONG DALAM UPAYA PATROLI PENCEGAHAN TERHADAP PENCURIAN DENGAN KEKERASAN DI WILAYAH HUKUM POLRES SORONG DITINJAU BERDASARKAN UNDANG-UNDANG NOMOR 2 TAHUN 2002 TENTANG KEPOLISIAN NEGARA REPUBLIK INDONESIA - Rerung, Kristianto; Murary, Weron; Renouw, Dian Mega Erianti (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Abstract: The problem of crime is a phenomenon that always occurs in urban and rural communities. Crime can arise as a result of individual or group dissatisfaction with the achievement of fulfilling their life needs. One of the crimes that has been widely reported in the last decade in Indonesia, especially in the Sorong Police area, is theft with violence. This research aims to determine the role of the Turjawali Unit of the Sorong Police Samapta Unit in efforts to prevent patrols against violent theft in the Sorong Police jurisdiction based on Law Number 2 of 2002 concerning the State Police of the Republic of Indonesia and the obstacles faced by the Turjawali Unit of the Sorong Police Samapta Unit in preventive patrol efforts against violent theft in the Sorong Police jurisdiction. The research method used is the empirical normative type, which was carried out at the Turjawali Unit, Sorong Police Samapta Unit. Data was obtained through primary data sources and secondary data sources using library study, interview and observation data collection techniques which were then analyzed using qualitative analysis. The research results obtained on the role of the Turjawali Unit of the Sorong Police Samapta Unit in this patrol are as a recipient of complaints for the community and as a source of information for the unit. This countermeasure is to prevent the meeting of intention and opportunity factors that allow criminal acts to occur. The role carried out by the Turjawali Unit of the Sorong Police Samapta Unit is of course also to support police actions in the form of preventive and repressive or prevention and handling. Meanwhile, the obstacles faced by the Turjawali Unit of the Sorong Police Samapta Unit in their efforts to prevent violent theft in the Sorong Police Legal Area are lack of personnel, lack of facilities and infrastructure and lack of community participation.Keywords: Police, Turjawali Unit, Samapta Unit, Theft with violence